Female Entrepreneurship in Morocco, Obstacles and Ways to Overcome Them - Amina Asli; Habiba Bensassi Nour (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Facing a labor market that is unable to absorb a growing demand, entrepreneurship and self-employment is an interesting path on many levels. In addition to being a real driver of growth and competitiveness, entrepreneurship is also a mean of self-realization, independence and personal growth.However, Women appear relatively few to engage in this career path. Indeed, the Association of Women Entrepreneurs “Association des Femmes Entrepreneures (AFEM)” estimates that the #of women entrepreneurs in Morocco does not exceed 10,000, which represents barely 0.5% of women's employment in the formal sector and about 10% of the #total enterprises. What are the reasons behind this fact-finding and how to overcome this existing situation? Several factors impeding women's entrepreneurship are noted in the literature. Some are personal; others are cultural or related to the general environment of entrepreneurship. This communication is meant to be an exploration of the different obstacles to women's entrepreneurship in Morocco, as well as actions to put in place to promote it. A sample survey will be conducted with a representative sample of women and stakeholders in Entrepreneurship ecosystem to identify the most influential factors and highlight the levers to be used to promote female entrepreneurship.
Keywords: 650; Employment; Female entrepreneurship; Obstacles; Promotion